2018
DOI: 10.31083/j.rcm.2018.02.893
|View full text |Cite
|
Sign up to set email alerts
|

Stress Cardiomyopathy in a Patient with Hypertrophic Cardiomyopathy: Case Presentation and Review of the Literature

Abstract: Stress cardiomyopathy and hypertrophic cardiomyopathy are two distinct entities with different pathophysiologic causes. In the recent medical literature their concurrency has been described. During the acute phase of a stress cardiomyopathy making the diagnosis of a concomitant hypertrophic cardiomyopathy may be challenging, and has important implications in both the acute and longterm clinical management. Herein, we present a case of a stress cardiomyopathy occurring in a patient with hypertrophic cardiomyopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Our literature search yielded case series [ 7 , 8 , 9 , 12 , 13 , 14 ], case reports [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], one prospective cohort study [ 39 ], and one systematic review [ 40 ] that described cases of obstructive HCM with LV ballooning overlapping with neurohumoral Takotsubo syndrome (TTS). We propose key features to differentiate these diagnoses, as shown in Fig.…”
Section: Case Series and Case Reports Of Left Ventricular (Lv) Balloo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search yielded case series [ 7 , 8 , 9 , 12 , 13 , 14 ], case reports [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], one prospective cohort study [ 39 ], and one systematic review [ 40 ] that described cases of obstructive HCM with LV ballooning overlapping with neurohumoral Takotsubo syndrome (TTS). We propose key features to differentiate these diagnoses, as shown in Fig.…”
Section: Case Series and Case Reports Of Left Ventricular (Lv) Balloo...mentioning
confidence: 99%
“…Although the above findings may be useful for differentiating TTS from HCM with latent obstruction and apical ballooning, the clinical evolution of the disease process over time is often the most useful for differentiating the two entities. Several case reports found that patients who presented acutely with LV apical ballooning and were diagnosed with TTS continued to show septal hypertrophy, LVOT obstruction, and mitral pathology for several weeks to months after initial presentation, and were ultimately diagnosed as HCM with obstruction [ 12 , 25 , 26 , 37 ]. Therefore, the continued evidence of such abnormalities on imaging after acute improvement of wall motion abnormalities would indicate the presence of underlying HCM.…”
Section: Clinical Course and Additional Diagnosticsmentioning
confidence: 99%